Shifting tides: A survey analysis of urologists’ evolving attitudes toward focal therapy for prostate cancer - Jason Koehler; Alon Lazarovich; Shima Tayebi; Vijay Viswanath; Arvin George; Wei-Wen Hsu; Abhinav Sidana (Indian Journal of Urology)
Introduction: Focal therapy (FT) is emerging as an alternative to radical treatment for prostate cancer (CaP). The purpose of this study is to assess the current perceptions of FT amongst urologists. Methods: A 22-item questionnaire was e-mailed to members of the American Urological Association. Multivariate logistic regression analysis was used to identify predictors of FT utilization. Results were compared to a previous survey from 2019. Results: Two hundred and sixty-four responses were recorded. Less than half (115/264, 43.6%) of respondents utilize FT; among them, 42% perform FT on more than 10 patients/year. Reasons for avoiding FT included: lack of experience (51.8%), belief that CaP is multifocal (46.0%), and lack of infrastructure (43.1%). The most common modalities for FT were high-intensity focused ultrasound (63.4%) and cryoablation (47.3%). Preferred patients for FT were primarily unilateral/anterior only Gleason Grade Group 2 (95/110, 86.4%). A fellowship training in urologic oncology (odds ratio [OR] = 2.86, P = 0.008) and seeing more than 10 CaP patients per month (OR = 2.46, P = 0.002) were associated with greater utilization of FT. Most respondents (85.4%) cited better imaging methods as a factor that has increased FT utilization. Compared to a previous survey, a higher number of respondents (43% vs. 24%) utilize FT and more respondents believe in the “index lesion theory.” Conclusions: Less than half of the respondents utilize FT in their practice. Fellowship training in urologic oncology and a higher volume of CaP patients were correlated with FT utilization. As urologists gain more experience, the trend of further utilization of FT for CaP may continue.